On the elastic equilibrium of a piecewise homogeneous plane with a crack at the corner point of the interface - Kaminsky, A.A.; Kipnis, L.A.; Polischuk, T.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The static symmetric problem of the theory of elasticity for a piecewise homogeneous isotropic plane with the interface in the form of angle sides and a crack at the corner point is considered. The exact solution of the Wiener—Hopf equation of the problem is constructed. The stress intensity factor at the crack tip is determined.